1991
DOI: 10.1099/0022-1317-72-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characterization of the Nucleoprotein and Matrix Protein of Influenza C Virus with Monoclonal Antibodies

Abstract: Monoclonal antibodies against the nucleoprotein (NP) and matrix (M) protein of influenza C virus were prepared and characterized. At least two non-overlapping or partially overlapping antigenic sites were delineated on each of the proteins by competitive binding assays. Western blot analysis showed that two antigenic sites on the M protein were highly resistant to conformational changes whereas two sites on NP were sensitive. No antigenic variation was seen in either the NP or the M protein when the reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 43 publications
(31 reference statements)
1
32
0
Order By: Relevance
“…The latter finding provided evidence for the requirement of nuclear function for influenza C virus replication. In addition, the association of M1 with the nucleoli was observed in the C/Yamagata/1/88-infected cells, a phenomenon that remains to be elucidated with respect to viral replication (Sugawara et al, 1991).…”
Section: Characteristics Of the M1 And Cm2 Proteins 31 M1 Proteinmentioning
confidence: 96%
See 2 more Smart Citations
“…The latter finding provided evidence for the requirement of nuclear function for influenza C virus replication. In addition, the association of M1 with the nucleoli was observed in the C/Yamagata/1/88-infected cells, a phenomenon that remains to be elucidated with respect to viral replication (Sugawara et al, 1991).…”
Section: Characteristics Of the M1 And Cm2 Proteins 31 M1 Proteinmentioning
confidence: 96%
“…Furthermore, Yokota et al identified the M1 protein synthesized in C/Ann Arbor/1/50-infected MDCK cells (Yokota et al, 1981). To characterize the protein, the monoclonal antibodies against M1 have been produced (Sugawara et al, 1991). Using a panel of the nine MAbs against M1, the M1 protein was shown to contain two non-overlapping antigenic regions that are highly resistant to conformational changes, and to exhibit no antigenic variations among 23 influenza C virus strains isolated over 41 year period.…”
Section: Characteristics Of the M1 And Cm2 Proteins 31 M1 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Their specificity was confirmed by radioimmunoprecipitation using lysates of [aSS]methionine-labelled HMV-II cells infected with C/AA/50 or C/MS/80 as antigens as described by Sugawara et al (1991) …”
mentioning
confidence: 99%
“…MAbs against the HE protein of C/AA/50 or C/Mississippi/I/80 (C/MS/80) virus were produced according to methods of Hongo et al (1986) and Sugawara et al (1991). Their specificity was confirmed by radioimmunoprecipitation using lysates of [aSS]methionine-labelled HMV-II cells infected with C/AA/50 or C/MS/80 as antigens as described by Sugawara et al (1991) …”
mentioning
confidence: 99%